Assessment of the effectiveness of CIS-CSA bundled practices for improving climate risk management in Nigeria - Mvuyibwami, Patrick; Kagabo, Desire M; Eitzinger, Anton; Muhigirwa, Mireille U. (2024)
Climate change poses severe risks to Nigeria’s agriculture, threatening food and financial security due to rising temperatures, erratic rainfall, and flooding. To strengthen resilience, the Alluvial MasterCard project, in collaboration with partners, implemented training workshops on Climate Information Services (CIS) and Climate-Smart Agriculture (CSA). Sixty-six master trainers were equipped to reach over 5,000 farmers with innovations such as drought-resistant crops, flood-resistant fish species, and climate-smart practices. A follow-up survey revealed improvements in farmers’ adaptive capacities but highlighted gaps in inclusivity and effectiveness. Findings stress the need for more tailored, context-specific training approaches to ensure broader and more equitable impacts.